Stereotyped B-cell response that counteracts antigenic variation of influenza viruses - Tonouchi, Keisuke; Adachi, Yu; Moriyama, Saya; Sano, Kaori; Tabata, Koshiro; Ide, Keigo; Takeyama, Haruko; Suzuki, Tadaki; Takahashi, Yoshimasa (International immunology, 2020)
Abstract Influenza A subtypes are categorized into group 1 and group 2 based on the hemagglutinin (HA) sequence. Owing to the phylogenetic distance of HAs in different groups, antibodies that bind multiple HA subtypes across different groups are extremely rare. In this study, we demonstrated that an immunization with acid-treated HA antigen elicits germinal center (GC) B cells that bind multiple HA subtypes in both group 1 and group 2. The cross-group GC B cells utilized mostly one VH gene (1S56) and exhibited a sign of clonal evolution within GCs. The 1S56-lineage IgGs derived from GC B cells were able to bind to HA protein on the infected cell surface but not to the native form of HA protein, suggesting the cryptic nature of the 1S56 epitope and its exposure in infected cells. Finally, the 1S56-lineage IgGs provided protection against lethal infection in an Fc-dependent manner, independent of the virus-neutralizing activity. Thus, we identified 1S56-lineage antibodies as a unique stereotype for achieving cross-group influenza specificity. The antigens exposing the 1S56 epitope may be good candidates for broadly protective immunogens.